Sigmund Freud dan Homoseksual (Sebuah Tinjauan Wacana Keislaman) - Dawam, Ainurrafiq (Musawa Jurnal Studi Gender dan Islam, 2003)
It is very interesting to bring discourse on homosexuality and lesbianism, particularly from a psychological perspective into the arena of Islamic discourse. Study of homosexuality and lesbianism becomes even more interesting when we try to elaborate on the psychological theories of sexuality from the expert and pioneer of psychoanalysis, Sigmund Freud. Freud was considered by some as anti-God, anti-establishment, anti-argument, anti-consciousness and anti-rationality. This was because Freud created inner psychology, which not only examined the visible indications of the soul, but also those things connected to dreams, hysteria and imaginings. This article discusses the phenomena of homosexuality and lesbianism from a psychological perspective, mainly focusing on the theories of Freud. This is because Sigmund Freud is the psychologist who proposed psychoanalysis, which introduced and spread.